COMPATIBILITY OF THE CULTURE OF INTERNATIONAL TOLERANCE WITH MORALITY - Xoliqov Yunus Ortiqovich (Journals Park Publishing, 2023)
This article highlights the philosophical significance of shaping a culture of tolerance in young people. The role of the family and society in the formation of a culture of tolerance among young people in connection with morality, as well as the large-scale work carried out in our country are highlighted.
Keywords: tolerance, culture, enlightenment, globalization, mentality, national values, traditions, science, nation, ethnicity, pragmatism, strategy, pluralism, popular culture, security